The origin of black and white coloration of the Asian tiger mosquito Aedes albopictus (Diptera: Culicidae) - Manuela Rebora; Gianandrea Salerno; Silvana Piersanti; Alexander Kovalev; Stanislav N. Gorb (Beilstein Journal of Nanotechnology, 2023)
Micro- and nanostructures of the white and black scales on the tarsi of the mosquito Aedes albopictus are analysed using scanning electron microscopy, transmission electron microscopy, and fluorescence microscopy. Reflectance spectra of the white areas are measured. No clear difference is present in the morphology of micro- and nanostructures of black and white scales in SEM and TEM, but black scales contain a dark pigment. The white colour of the scales has a structural origin. The structural white produced by the micro- and nanostructures of the scales on the tarsi of Ae. albopictus appears bright and is angle-dependent, since the reflected light changes according to the angle detection and according to the tarsus orientation. The optical appearance of the scale system of Ae. albopictus has a complex nature and can be explained by the combination of several effects. Among them, multiple refraction and reflection on the micro- and nanostructures of the scales are mainly responsible for the white appearance. The results suggest that mosquito scales, in addition to their superhydrophobic function, produce structural white. The biological role of white and black patches in mate recognition and defensive behaviour in the mosquitoes of the genus Aedes is hypothesized.